Thermodynamically consistent elasto-plastic microplane formulation for fiber reinforced concrete. (1st March 2016) - Vrech, Sonia; Etse, Guillermo; Caggiano, Antonio
Abstract: In this work a thermodynamically consistent elasto-plastic microplane constitutive theory, aimed at simulating the failure behavior of Steel Fiber Reinforced Concrete (SFRC), is developed. The continuum (smeared crack) formulation, based on the microplane theory, assumes a parabolic maximum strength criterion in terms of normal and shear (micro-)stresses evaluated on each microplane to simulate the failure behavior of concrete. In the high confinement regime, a non-associated plastic flow rule is also defined in terms of microplane stresses. The well-known "Mixture Theory" is considered to account for the presence of fibers in concrete matrix. The interaction between steel fibers and cracked concrete in the form of fiber-to-concrete bond-slip and dowel mechanisms is taken into account. The complete formulation is fully consistent with the thermodynamic laws. After describing the proposed constitutive theory, numerical analyses at constitutive level of SFRC failure behavior are presented and discussed. Thereby, the variations of the fracture energy, post-peak strength and cracking behavior with the fiber contents are evaluated and compared against experimental data. The attention also focuses on the evaluation of the sensitivity of SFRC failure predictions with the proposed constitutive model regarding fiber orientation on one hand, and the bond-slip bridging actions and dowel mechanism on the other hand.